DEVELOPMENT OF A COLOR PIXEL PROCESSING ALGORITHM FOR THE BIG FIVE PERSONALITY TRAITS SELF-EVALUATION MODEL: DEVELOPMENT OF A COLOR PIXEL PROCESSING ALGORITHM FOR THE BIG FIVE PERSONALITY TRAITS SELF-EVALUATION MODEL - Atanasov, Valentin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
A series of studies establishes the foundation for the development of algorithms, the potential application of which will facilitate the practical implementation of a model based on the Big Five Personality Traits (BFPT). The creation of algorithmic code would provide a programming toolkit applicable across various domains of human activity, specifically for the expert evaluation of individual behavior. The proposed algorithm is grounded in classification based on color ranges (and by extension, personality types), implemented through programmatically defined coded logic. The fundamental steps of the algorithm's logic are outlined. For each personality trait — Openness, Conscientiousness, Extraversion, Agreeableness, Neuroticism — a set of reference HSL (Hue, Saturation, Lightness) colors is redefined.